Debunking the trends and implications of non-bank financial institutions in Bangladesh financial sector - Chowdhury, Tanbir Ahmed; Snigdha, Nishat Tamanna; Chowdhury, Tahiya Ahmed (Asian Economic and Financial Review, 2025)
The purpose of this study is to analyze the trends and implications of selected NBIFs in Bangladesh’s financial sector. Several variables were employed to examine the performance of the selected NBFIs, such as total capital, debt to total capital, debt to equity, capital adequacy ratio, total deposits, total loans, loan/deposit ratio, return on deposits, net interest margin, bad debts, ROI, ROA, ROC, net income, etc. Statistical measures like trend equations, R-squared, and correlation matrices were used to analyze the data. To estimate the implications of NBFIs in Bangladesh’s financial sector, nine hypotheses were also tested. Seventeen different significant NBIF variables were tested using 85 trend equations and R-squared values. Their steadily rising net income, ROE, and ROA over time indicate their financial stability. NBFIs face difficulties due to restricted regulation, inefficient credit, and a lack of digital transformation. It is anticipated that the study’s correlation matrix and trend analysis results will guide the selected NBFIs in Bangladesh to improve their performance. The employed methods should focus on good governance, innovation, and technology integration. This approach will not only strengthen NBFI growth but also contribute to the overall economic landscape of Bangladesh.